How can Community-Based Participatory Research Address Hate Crimes and Incidents? - Turlock, Landon; Mayan, Maria (Engaged Scholar Journal, 2023)
Reports of hate crimes in Canada have increased by 72% from 2019 to 2021 (Moreau, 2022). Hate crimes harm those directly victimized and members of targeted communities (Erentzen & Schuller, 2020; Perry & Alvi, 2011). Many Canadian stakeholders advocate for increased community engagement in preventative and responsive interventions to this increasing concern. This article poses that Community-Based Participatory Research (CBPR) is an appropriate approach for further exploring hate crimes and incidents and suggests strategies for this area of study, including: building community partnerships; advocating for trauma-informed practices; prioritizing cultural humility and intersectionality; preparing for lengthy pre-participation communication with potential participants; anticipating out-of-scope volunteer participants; and accounting for unanticipated actions of participants.